Lakukullus anatisrostratus, gen. et sp. nov., a new massive nothrotheriid sloth (Xenarthra, Pilosa) from the middle Miocene of Bolivia - Pujos, François Roger Francis (2014)
Xenarthra constitute one of the most representative groups of South American endemic mammals. The armored Cingulata is recorded beginning in the Itaboraian SALMA (lower Eocene; Pujos et al., 2012). Its sister group is Pilosa, which includes Tardigrada, the sloths, and Vermilingua, the South American anteaters. Sloths appear during the Eocene–Oligocene transition (Tinguirirican SALMA) in Chile, represented by Pseudoglyptodon (McKenna et al., 2006). The late Oligocene Deseadan SALMA saw the emergence of Mylodontidae (e.g., Octodontotherium and Orophodon) and Megalonychidae (e.g., Deseadognathus) in Patagonia and the Bolivian altiplano (Pujos et al., 2007). Megatherioidea appear later during the middle Miocene, Megatheriidae in the Santacrucian SALMA (i.e., Megathericulus; Pujos et al., 2013), and Nothrotheriidae in the Huayquerian SALMA (i.e., Mionothropus; De Iuliis et al., 2011). According to De Iuliis et al. (2011), Nothrotheriidae is supported by 13 unequivocal synapomorphies and includes at least five genera: Mionothropus, Pronothrotherium, Thalassocnus, Nothrotherium, and Nothrotheriops. Several possible nothrotheriids, generally represented by poor material, have been described from Colombia (Huilabradys), Argentina (e.g., Nothropus, Chasicobradys, Amphibradys, and Xyophorus), and Bolivia (Xyophorus and Hiskatherium). Those from Argentina are poorly diagnosed, cannot certainly be differentiated morphologically from other taxa such as Hapalops, and are likely invalid. Nothropus priscus is exclusive to the Pleistocene of Argentina and is not present in the Amazon (see De Iuliis et al., 2011, for further details).